Effects of multi‐metal exposure on the risk of diabetes mellitus among people aged 40–75 years in rural areas in southwest China - Jing Zhang; Huanhuan Yin; Xuemei Zhu; Rong Xiang; Yeqiu Miao; Yu Zhang; Yang Song; Jinyao Chen; Lishi Zhang (Journal of Diabetes Investigation, 2022)
Abstract Aims/Introduction Metals play an important role in diabetes mellitus. This cross‐sectional study aimed to evaluate the overall, individual and interactive effects of multi‐metal exposure on the prevalence of diabetes mellitus, impaired fasting glucose (IFG) rate and fasting blood glucose (FBG) levels. Materials and Methods The FBG levels of a study population from a cadmium (Cd)‐polluted area (n = 250) and an unpolluted area (n = 204), and the metal levels, including magnesium, calcium (Ca), iron (Fe), zinc (Zn), arsenic (As), Cd, copper and lead (Pb) in blood and urine were detected. The study population was divided into a normal fasting glucose group, an IFG group and a diabetes mellitus group on the basis of FBG levels. Results The IFG rate and diabetes mellitus prevalence were negatively associated with blood Cd and urine Zn levels (IFG rate: odds ratio [OR] 0.780, 95% confidence interval [CI] 0.655–0.928; OR 0.622, 95% CI 0.465–0.831. Diabetes mellitus prevalence: OR 0.506, 95% CI 0.288–0.888; OR 0.609, 95% CI 0.395–0.939), the IFG rate was positively associated with urine Fe levels (OR 1.876, 95% CI 1.290–2.778), and diabetes mellitus prevalence was positively associated with urine Pb and blood Fe levels (OR 1.185, 95% CI 1.022–1.376; OR 1.008, 95% CI 1.001–1.014). A linear negative correlation was observed between FBG levels and blood Cd, and non‐linear inverted U‐shaped associations were found between FBG levels and Zn, Pb and copper in urine. Conclusions This research suggests that multi‐metal exposure, especially Cd, Fe, Zn, copper and Pb, is linked to diabetes mellitus, and the interactive effects of multiple metals require further exploration.